Advancing diversity, inclusion, and social justice through human systems engineering - Roscoe, Rod D.; Chiou, Erin K.; Wooldridge, Abigail R. (Boca Raton : CRC Press, 2020)
"Advancing Diversity, Inclusion, and Social Justice through Human Systems Engineering highlights how scholars and practitioners of HSE (inclusively defined to span many fields) can apply their theories and methods to understand and support healthy communities, include and empower diverse populations, and inspire strategies for a more inclusive future. This volume brings together experts from human factors, ergonomics, psychology, human-computer interaction, and more to demonstrate how these fields can be applied to societal challenges and solutions. Through a blend of research reports, literature reviews, and personal narratives, this volume explores these issues from the individual to the global scale, across diverse populations, and across multiple continents"--
Human Systems Engineering for Societal Transformation : A Tale of Two Cities / Nancy Cooke -- Inclusive Decision Making : Applying Human Factors Methods to Capture the Needs and Voices of Marginalized Populations / Jacklin Stonewall, Michael C. Dorneich, Linda Shenk, Caroline C. Krejci, and Ulrike Passe -- HFE in Underdeveloped Countries : How Do We Facilitate Equitable, Egalitarian, and Respectful Progress? / Andrew Thatcher and Andrew Todd.
OCLC-licensed vendor bibliographic record.
Keywords: System design -- Social aspects; Human engineering -- Research -- Social aspects; Systems engineering -- Social aspects; Multiculturalism; Social justice; TECHNOLOGY / General; TECHNOLOGY / Engineering / General; TECHNOLOGY / Manufacturing